(untitled) (مجلة البحوث الأكاديمية, 2025)
Cutaneous leishmaniasis (CL) is a vector-born parasitic diseaseendemic in many Mediterranean and Middle Eastern regions. This study describes the epidemiological characteristics of CL in Al-Khums City, Libya, between 2024 and 2025. Data from 802 confirmed cases were analyzed according to gender, age, region, and monthly distribution. Males accounted for 61.7% of cases. The most affected age group was 45–54 years (16.2%). Seasonal variationwas marked, with case peaks in December 163 ( 20.3%)and January 209 (26.0%) . Pearson correlation revealed a strong inverse relationship between monthprogression and CL incidence (r = −0.96, p = 0.001). Al-Amamera, Al-Daawon, and Al- Ma‘qula were identified as major hotspots. Findings highlight significant seasonal and spatial clustering of CL and underscore the need for targeted winter-season vector control.